“Not Every Advisor Is for Me, but Some Are”: Black Men’s Academic Advising Experiences during COVID-19 - Jesse R. Ford; Dawn Y. Matthews; Derrick M. Woodard; Cassandra R. Kepple (Education Sciences, 2023)
Contemporary research indicates that Black American men encounter multiple obstacles in higher education settings. Understanding the complexities of how Black men perceive and make sense of academic environments requires addressing a number of elements that influence their academic success. The purpose of this study is to investigate the academic advising challenges faced in virtual environments by Black men during the COVID-19 pandemic. This qualitative case study provides detailed accounts of ten Black men navigating academic advising practices in a virtual setting at large research one historically white institution using focus groups as a method of data collection. Implications and suggestions for future research highlight the significance of supporting Black men in virtual academic advising spaces to create equitable and sustainable practices.